A study on cost-effective and colorless wavelength-division-multiplexed passive optical networks - Xiong, Fei (2014)
To meet the explosive demand of high-speed Internet access, future-proofing infrastructure for access networks which are capable of being fully scalable in capacity to each subscriber is vital. Wavelength-division-multiplexed passive optical network (WDM-PON) is considered as the ultimate solution for next-generation access networks thanks to the unlimited bandwidth guaranteed by a dedicated wavelength (or a pair of wavelength) for each subscriber. However, some challenging issues are still blocking the way of mass deployment of WDM-PON systems. This dissertation is devoted to developing some enabling solutions for these challenging issues in WDM-PON technologies, including 1) implementation of cost-effective colorless optical network units (ONUs) and 2) delivery of broadcast service over WDM-PON architectures. The primary concern in WDM-PON implementation is the cost-efficiency of ONUs. Self-seeding of reflective semiconductor optical amplifiers (RSOAs) has been demonstrated as a cost-effective method to realize colorless ONUs in WDM-PONs. This dissertation first provides an in-depth study of the transmission performance of self-seeded RSOA-based WDM-PONs. The impact of various system parameters on the system performance are investigated through experiments. The bit rate of a self-seeded RSOA is increased by boosting the seeding power as well as employing electronic equalization. A low-cost colorless WDM-PON system is proposed where 5-Gb/s downstream transmission is enabled using self-seeded RSOAs and 1.25-Gb/s upstream transmission is achieved using remote-seeded RSOAs. Another work dedicated to develop low-cost colorless ONUs is to utilize a multimode-injected Fabry-Perot laser diode (FP-LD) as the remote seeding light in carrier-distributed WDM-PON architectures. The feasibility of the proposed scheme is demonstrated by the improved transmission performance when compared to the system in which an amplified spontaneous emission source is adopted as the remote seeding light. The latter part of the dissertation discusses two new techniques to enable broadcast service over WDM-PON architectures. One of the broadcast-capable WDM-PONs is based on polarization multiplexing technique. The downstream unicast and broadcast data are carried by two orthogonally polarized optical beams. Not only does this technique support broadcast services without allocating additional wavelength channels and using high-frequency subcarrier multiplexing, but it also depolarizes the seeding light to FP-LDs for upstream transmission. However, active polarization tracking is required to demultiplex the two polarization-multiplexed signals at each ONU, which may hinder the real deployment of such a system. To improve the cost-effectiveness, another broadcast-capable WDM-PON based on offset polarization multiplexing is proposed and demonstrated. In this WDM-PON architecture, the downstream differential phase-shift keying (DPSK)-formatted unicast and broadcast signals are offset polarization-multiplexed at the central office and demultiplexed and detected at the ONUs without resorting to any polarization tracking. Meanwhile, the offset polarization-multiplexed downstream signals could also facilitate the external injection of polarization-sensitive FP-LDs for colorless operation. Successful transmissions of 10-Gb/s downstream unicast and broadcast DPSK signals as well as 2.5-Gb/s upstream signal over a 20-km standard single-mode fiber are experimentally demonstrated.